2019
DOI: 10.1093/brain/awz045
|View full text |Cite|
|
Sign up to set email alerts
|

Heterogeneous clinical phenotypes and cerebral malformations reflected by rotatin cellular dynamics

Abstract: See Uzquiano and Francis (doi: ) for a scientific commentary on this article. Mutations in RTTN , which encodes Rotatin, give rise to various brain malformations. Vandervore et al. reveal mitotic failure, aneuploidy, apoptosis and defective ciliogenesis in patient cells. Rotatin binds to myosin subunits in the leading edge of human neurons, which may explain the proliferation and migration defects observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 56 publications
2
37
5
Order By: Relevance
“…A large number of neurological disease-linked genes regulate signaling pathways affecting myosin function, whereas MYH mutations are associated with intellectual disability, autism, and schizophrenia. NMII also interacts with rotatin, whose mutations cause microcephaly and intellectual disability, and tau, a central protein in AD and frontotemporal dementias [ 149 , 150 ]. The contributions of these mutations to myosin dysfunction in neurological and neuropsychiatric diseases need further confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of neurological disease-linked genes regulate signaling pathways affecting myosin function, whereas MYH mutations are associated with intellectual disability, autism, and schizophrenia. NMII also interacts with rotatin, whose mutations cause microcephaly and intellectual disability, and tau, a central protein in AD and frontotemporal dementias [ 149 , 150 ]. The contributions of these mutations to myosin dysfunction in neurological and neuropsychiatric diseases need further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…A similar phenotype is partially modeled by germline deletion of Myh9 in mice [ 44 ], which suggests that loss of Myh function causes severe developmental cerebral defects. More recent proteomic studies have identified NMIIA, B, and C as binding partners of rotatin ( RTTN ) , the gene of which is mutated in some cerebral pathologies, such as severe intellectual disability, cortical malformation, microcephaly, and polymicrogyria with seizures [ 149 ]. Although the specific mechanisms by which rotatin mutations trigger neurodevelopmental malformations remain unclear, it is tempting to speculate that these defects could be partially mediated by NMII.…”
Section: Non-muscle Myosin II In Neurological and Neurodegenerativmentioning
confidence: 99%
“…WES data analysis and filtering of variants were carried out as previously described (Bogershausen et al, 2015). RT‐PCR was performed as described by Vandervore et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation process include accurate classification based on neuroimaging analysis, detailed family history and a search for gestational insults as possible non-genetic causes of the malformation. Dr. Mancini and her team were able to link monogenetic mutations, chromosomal anomalies and copy number variations to patients presenting various MCDs including microcephaly, lissencephaly, pachygyria, subcortical band heterotopia, cobblestone-type lissencephalies, polymicrogyria (PMG) and schizencephaly (de Wit et al, 2008; Meuwissen et al, 2016; Oegema et al, 2017; Dobyns et al, 2018; Vandervore et al, 2019). In this process, the availability of next generation sequencing tools, open access databases allowing exchange of variants and the multidisciplinary interaction at local and international level have proved great effectiveness.…”
Section: Malformations Of Cortical Development (Mcds): Classificationmentioning
confidence: 99%